A Note on Entrepreneurial Risk, Capital Market Imperfections, and Heterogeneity - Luo, Yulei (2012)
Empirical evidence shows that entrepreneurs hold a large fraction of wealth, have higher saving rates than workers, and face substantial uninsurable entrepreneurial and investment risks. This paper constructs a heterogeneous-agent general equilibrium model with uninsurable entrepreneurial risk and capital-market imperfections to explore the implications of uninsurable entrepreneurial risk for wealth distribution and aggregate activity in an incomplete market economy. It is shown that entrepreneurial risk can substantially affect both the wealth distribution and the macroeconomy.